2023
DOI: 10.1021/acs.chemmater.3c01027
|View full text |Cite
|
Sign up to set email alerts
|

Production of Photonic Supraballs Composed of Single-Crystalline Colloidal Arrays through Osmosis-Induced Consolidation

Abstract: Photonic supraballs have been designed by evaporation-induced crystallization of colloidal particles confined in emulsion droplets for various applications. However, it has been a challenge to exclusively produce a single-crystalline structure in a short consolidation time due to droplet-by-droplet variation in the evaporation rate. Here, we suggest a pragmatic osmotic extraction of water from emulsion droplets to achieve a consistent rate of consolidation and improve the selectivity of crystalline structures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…We optically examined this type of cluster with a diameter of 260 nm, as shown in Figure a, and confirmed the presence of parallel orange lines. These striped reflections have been observed in some literature. , These line reflections originate from the {101̅0} plane of the hcp lattice, which includes the (011̅0) and (11̅00) planes related by 60° rotation with a rotation axis in ⟨0001⟩ direction. Thus, when the colloidal cluster shown in Figure a is rotated with the rotation axis normal to the orange lines, the reflection intensity is expected to increase and decrease with a period of 60° at the rotation angle.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We optically examined this type of cluster with a diameter of 260 nm, as shown in Figure a, and confirmed the presence of parallel orange lines. These striped reflections have been observed in some literature. , These line reflections originate from the {101̅0} plane of the hcp lattice, which includes the (011̅0) and (11̅00) planes related by 60° rotation with a rotation axis in ⟨0001⟩ direction. Thus, when the colloidal cluster shown in Figure a is rotated with the rotation axis normal to the orange lines, the reflection intensity is expected to increase and decrease with a period of 60° at the rotation angle.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have shown that spherical colloidal clusters have different particle arrangements, such as fcc and icosahedral-type structures, and the structural differences can be attributed to the experimental conditions applied during the preparation processes. When a water droplet rapidly shrinks upon heating, clusters with onion-like structures are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal arrays have been produced in a microbead format using emulsion droplets, offering structural colorants in photonic inks, which are potentially useful for structural color printing. For example, colloidal particles self-assemble within the droplets through enrichment by evaporation or osmotic extraction. Although these photonic microspheres, composed of close-packed arrays, exhibit structural colors, the colloidal assembly requires a long time for crystallization, and the microspheres have low mechanical stability due to the absence of particle binders, thereby restricting their applications. To overcome these limitations, photonic microspheres with non-close-packed arrays in a solid matrix have been developed. ,, Silica particles dispersed in polymerizable resins spontaneously form non-close-packed arrays by interparticle repulsion, which are captured in the polymeric matrix by in situ polymerization, reducing production time and securing high mechanical stability.…”
Section: Introductionmentioning
confidence: 99%